PENERAPAN USABILITY PADA APLIKASI C-ACCESS KAI COMMUTER MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Evy Nurmiati; Eliana Saputri (Indragiri Islamic University, 2024)
The use of mobile applications in various sectors, including transportation, has become an important part of everyday life. One example of an application used in transportation is the C-Access KAI Commuter application, which was developed by PT Kereta Api Indonesia (Persero). This research aims to measure the level of usability of the C-Access application using System Usability Scale (SUS) analysis, and also examine whether the updates made by KAI to the C-Access application can actually increase user satisfaction. The research method used is a quantitative descriptive approach, aimed at providing a structured, accurate and up-to-date understanding of the object under study. Data collection was carried out using a questionnaire created with Google Forms and distributed to 50 selected respondents. The findings of this research indicate that the C-Access application shows usability with an Acceptability Score of